Multilayer-Coated Tablet of Clopidogrel and Rosuvastatin: Preparation and In Vitro/In vivo Characterization - Ki-Soo Seo; Hyo-Kyung Han (Pharmaceutics, 2019)
The acid lability of rosuvastatin hinders the preparation of mixed combination formulations of rosuvastatin with acidic drugs such as clopidogrel. Therefore, the purpose of this study was to develop a multilayer-coated tablet that avoids physicochemical interactions between rosuvastatin and clopidogrel. Among the tested hydrophobic materials, glyceryl behenate was most effective at inhibiting the production of lactone, the acid degradation product of rosuvastatin. Therefore, the multilayer-coated tablet included a hydrophobic separation layer consisting of glyceryl behenate between the clopidogrel core tablet and the rosuvastatin coating layer. In order to prevent delayed dissolution by the stable hydrophobic separation layer, crospovidone was added into the clopidogrel core tablet as an effective disintegrant. Copovidone was also added to the coating layer of rosuvastatin, achieving a dissolution profile comparable to that of the reference drug, Crestor®. The resulting multilayer-coated tablet exhibited similar pharmacokinetic profiles to those of reference drugs (Plavix® and Crestor®) in beagle dogs, and there was no statistically significant difference in the maximum plasma concentration (Cmax), the time to reach the maximum plasma concentration (Tmax), or the area under the plasma-concentration time curve (AUC) between the test and reference formulations. The storage stability tests showed that the amounts of acid degradation products and total impurities were comparable to that of the reference drug. In conclusion, the present study successfully developed a stable multilayer-coated tablet containing both clopidogrel and rosuvastatin that may improve the patient compliance in combination therapy for cardiovascular diseases.